Penerapan Model Pembelajaran Kooperatif Tipe Stad untuk Meningkatkan Kemampuan Belajar Siswa dalam Pembelajaran Teks Drama pada Siswa Kelas VIII SMPN 7 Muaro Jambi - Putri, Mutiara Defrisa; D, Yusra; Rahmawati, Rahmawati (Jurnal Ilmiah Dikdaya, 2024)
This research aims to describe the use of the STAD type cooperative learning model to improve students' learning abilities in learning drama texts in class VIII students at SMP Negeri 7 Muaro Jambi. The main strength of the STAD type cooperative learning model lies in students' learning skills in studying the characteristics of linguistic elements and rules in drama texts. This research was carried out at SMP Negeri 7 Muaro Jambi. The research sample was class VIII D students, totaling 30 students. The research method used is a quantitative method and a type of pre-experimental research design. Data collection was carried out by observing and testing students' abilities in studying the characteristics of linguistic elements and rules in drama texts. Data analysis using SPSS 21. The research results obtained were student grades which were influenced by the use of the STAD type cooperative learning model on the learning outcomes of class VIII students at SMP Negeri 7 Muaro Jambi. The results of data analysis show that the average post-test score is higher than the average pre-test score. The pre-test results showed that the highest score was 14 while the lowest score was 8. After being given treatment, it showed an improvement with the highest score being 19 and the lowest being 14. Hypothesis testing was carried out using the t-test. From the calculation of the t-test results on pre-test and post-test data, it shows an increase. It is known that the Sig value. (2-tailed) of 0.000 <0.005, it can be concluded that there is a real difference between student learning outcomes in pre-test and post-test data. Thus, the alternative hypothesis (Ha) is accepted. This proves that the STAD type cooperative learning model is effectively used to improve students' learning abilities. From the research results, teachers are expected to increase the procurement of learning models and media. With this, teachers are more creative and innovative in learning activities. The learning process also makes students not feel bored and fed up, which can increase their motivation to learn.